An Anti‐PSMA Bivalent Immunotoxin Exhibits Specificity and Efficacy for Prostate Cancer Imaging and Therapy. Issue 5 (22nd November 2012) - Zhang, Fayun; Shan, Liang; Liu, Yuanyi; Neville, David; Woo, Jung‐Hee; Chen, Yue; Korotcov, Alexandru; Lin, Stephen; Huang, Sophia; Sridhar, Rajagopalan; Liang, Wei; Wang, Paul C.
Abstract Prostate specific membrane antigen (PSMA) is overexpressed on prostate tumor cells and the neovascular endothelia various solid tumors. A bivalent immunotoxin generated by fusing a fold‐back single‐chain diabody derived from the Fv fragments of an anti‐PSMA monoclonal antibody with a truncated diphtheria toxin (DT) containing the activity and translocation domains [A‐dmDT390‐scfbDb(PSMA)] might be suitable for targeted therapy of tumors that overexpress PSMA. In this study, a PSMA‐positive and a PSMA‐negative prostate cancer cell lines were treated with immunotoxin A‐dmDT390‐scfbDb(PSMA) in order to study the tumor targeting specificity and therapeutic potential of the immunotoxin. The cellular uptake and selective toxicity of the immunotoxin were evident in monolayer cultures of PSMA‐positive LNCaP prostate cancer cells but not in cultures of PSMA‐negative PC‐3 prostate cancer cells. Cellular accumulation of A‐dmDT390‐scfbDb(PSMA) increased with increasing incubation times and concentrations in LNCaP cells. The proportion of apoptotic LNCaP cells increased upon incubation with increasing doses of the fold‐back immunotoxin. Optical imaging and MRI with the Alexa Fluor 680‐labeled A‐dmDT390‐scfbDb(PSMA) confirmed the specific targeting and therapeutic efficacy of this immunotoxin towards PSMA‐positive LNCaP solid tumor xenografts in athymic nude mice.